PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS FLIPBOOK PADA CAPAIAN PEMBELAJARAN PEWARNAAN RAMBUT SINGLE APLIKASI DI SMKN 1 PACITAN - Sekar Arum Ayu Kartika; Biyan Yesi Wilujeng; Maspiyah; Sri Usodoningtyas (Program Studi Pendidikan Tata Rias, 2025)
Effective learning necessitates creative media that can present content in a captivating and comprehensible way. This study was conducted to determine 1) the appropriateness of the educational media, 2) the cognitive achievements of the students, and 3) the feedback from students in class XI TKKR at SMKN 1 Pacitan. The method chosen is Research and Development (R&D) utilizing the ADDIE model, which includes five essential phases: Analysis, Design, Development, Implementation, and Evaluation. The flipbook was designed using Canva and then uploaded to the Heyzine platform, which resulted in an appealing and user-friendly digital book format. The validation process involves six evaluators, consisting of experts in content, media, and language. Data was gathered via observations, assessments of learning outcomes, and surveys regarding student responses. The evaluation of the flipbook-based interactive learning media resulted in an overall average rating of 4.64, classifying it as